2009
DOI: 10.1002/msc.158
|View full text |Cite
|
Sign up to set email alerts
|

‘Extra information a bit further down the line’: Rheumatoid arthritis patients' perceptions of developing educational material about the cardiovascular disease risk

Abstract: There is a need to develop educational material or programmes. Their design must consider factors which facilitate lifestyle change, such as motivation or receiving personalized advice, and factors that inhibit change, such as depression or fatalism. Emphasizing the positive effects that some CVD lifestyle changes may have on RA symptom control may be particularly persuasive. Group education would be a popular format. These findings can be directly translated into clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
(51 reference statements)
3
18
0
Order By: Relevance
“…Patients mention that meeting and talking to other peers is very helpful because (1) it gives rheumatoid arthritis patients a chance to mirror themselves and their own experience, (2) they can legitimize their experience with other rheumatoid arthritis patients, and (3) they can find role models showing it is possible to live a normal life with rheumatoid arthritis (John et al, 2009;Kristiansen et al, 2012a,b).…”
Section: Emotional Support Needsmentioning
confidence: 95%
See 1 more Smart Citation
“…Patients mention that meeting and talking to other peers is very helpful because (1) it gives rheumatoid arthritis patients a chance to mirror themselves and their own experience, (2) they can legitimize their experience with other rheumatoid arthritis patients, and (3) they can find role models showing it is possible to live a normal life with rheumatoid arthritis (John et al, 2009;Kristiansen et al, 2012a,b).…”
Section: Emotional Support Needsmentioning
confidence: 95%
“…Since it is known that rheumatoid arthritis is related to cardiovascular risks (CVR), patients expressed the need for professional to listen to their concerns about cardiovascular risk and for receiving advice about their uncertainties about CVR, for example ''Doing exercises which could help the heart, but not hinder rheumatoid arthritis'' (John et al, 2009). …”
Section: Information Needs About Cvrmentioning
confidence: 99%
“…A small proportion of our respondents were upset by the leaflet. This may have related to the fact that it ‘broke bad news’ about co‐morbid CVD associated with RA (John et al, ). The converse would be to adopt a more paternalistic view that patients could not cope with bad news (Coulter, ); however, this denies patients the opportunity to make informed decisions about their lifestyle (John et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mindful that the literature reports a potential incongruence between the information provided by health professionals and the information that patients request (Hirsh et al, ), it was felt important to have patient input both in the development of the leaflet and in its evaluation. Hence, qualitative research with stakeholders was performed, namely individual interviews with patients with RA and focus groups with relevant healthcare professionals (John et al, ). This revealed that patients were mostly unaware of the association between RA and CVD, but were interested in learning what could be done to address their risk, requesting ‘common sense’ advice, taking into account their RA (John et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation